2017
DOI: 10.1016/j.mri.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Image-based gradient non-linearity characterization to determine higher-order spherical harmonic coefficients for improved spatial position accuracy in magnetic resonance imaging

Abstract: Purpose Spatial position accuracy in magnetic resonance imaging (MRI) is an important concern for a variety of applications, including radiation therapy planning, surgical planning, and longitudinal studies of morphologic changes to study neurodegenerative diseases. Spatial accuracy is strongly influenced by gradient linearity. This work presents a method for characterizing the gradient non-linearity fields on a per-system basis, and using this information to provide improved and higher-order (9th vs 5th) sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…However, the results showed that the performance for the high‐order SH such as the 11th order was stable on the large FOV (e.g., 50‐cm DSV) but unstable at smaller FOVs (e.g., 30‐cm DSV). Moreover, fitting for higher‐order coefficients could be challenging because of the convergence difficulty in iterative algorithms . An investigation of the accuracy and stability of higher‐order SH was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the results showed that the performance for the high‐order SH such as the 11th order was stable on the large FOV (e.g., 50‐cm DSV) but unstable at smaller FOVs (e.g., 30‐cm DSV). Moreover, fitting for higher‐order coefficients could be challenging because of the convergence difficulty in iterative algorithms . An investigation of the accuracy and stability of higher‐order SH was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies used an iterative calibration process to obtain higher‐order SH coefficients for GNL modeling in a larger FOV. However, the results showed that the performance for the high‐order SH such as the 11th order was stable on the large FOV (e.g., 50‐cm DSV) but unstable at smaller FOVs (e.g., 30‐cm DSV). Moreover, fitting for higher‐order coefficients could be challenging because of the convergence difficulty in iterative algorithms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradient field map tensor can be generally expressed using spherical harmonic polynomial expansion . The model coefficients can be obtained using electromagnetic (EM) simulation or phantom calibration . In general, for conventional whole‐body systems, only model coefficients of odd‐orders (eg, 3 rd order, 5 th order, etc.)…”
mentioning
confidence: 99%
“…7,8 The model coefficients can be obtained using electromagnetic (EM) simulation or phantom calibration. 1,9,10 In general, for conventional whole-body systems, only model coefficients of odd-orders (eg, 3 rd order, 5 th order, etc.) are required for distortion correction when imaging the head.…”
mentioning
confidence: 99%